Festival encounters : theoretical perspectives on festival events - Duffy, Michelle (Michelle Elizabeth); Mair, Judith (London ; New York, N.Y. : Routledge, 2018)
"Festivals and events are of enormous significance to many communities around the world. They can have historic, religious, cultural and traditional significance, and they are also important parts of community building.This book focuses on these small-scale, non-metropolitan events (i.e. rural, regional and peri-urban) to explore the complex relationships between place, community and identity and the ways in which festival events bring these into being. By drawing on the notion of "encounter," this book examines how festivals and events can be seen primarily as spaces where different people meet. This notion of encounter helps us to understand how conviviality and social relations are developed, and what this then means in terms of social cohesion and social justice. It also draws on current theoretical and methodological approaches that can tell us about the role of festivals in contemporary life, and it includes the sensual approach, the geographies of affect and emotion, the notion of the right to the city and nonrepresentation theory.The book brings together these perspectives and examines their relevance in the community events context, identifying and discussing theoretical frameworks drawn from (including but not limited to) human geography, sociology, anthropology, leisure studies and urban planning, as well as tourism and event studies. For these reasons, Festival Encounters will be a valuable read for students and academics working on a wide range of disciplines."--Provided by publisher.
Approaches to festival research -- Encounter as our underpinning theory -- Rituals of community : encounters of cohesion and subversion -- Mobilities and the shaping of encounter -- Festivals, non-representation theory and encounter -- Festivals and social justice -- Social inclusion, social exclusion and encounter -- Festivals and social capital -- Encounter with past, present and future - Yakkerboo and the rural-urban fringe -- Experience! : the Casey Multicultural Festival : encounter with "the other" -- Clunes booktown festival : encounters with class mobilities -- Noosa Jazz Festival : encounter with the senses.
Keywords: Festivals -- Social aspects; Social participation; Group identity